2018
DOI: 10.1080/14686996.2018.1527645
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization and properties of selective laser melted maraging steel with different build directions

Abstract: A nearly fully dense grade 300 maraging steel was fabricated by selective laser melting (SLM) additive manufacturing with optimum laser parameters. Different heat treatments were elaborately applied based on the detected phase transformation temperatures. Microstructures, precipitation characteristics, residual stress and properties of the as-fabricated and heat-treated SLM parts were systematically characterized and analyzed. The observed submicron grain size (0.31 μm on average) suggests an extremely high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 201 publications
(92 citation statements)
references
References 41 publications
8
84
0
Order By: Relevance
“…In printed samples where layering is perpendicular to the direction of the applied load, failure occurs before samples printed such that layers are parallel to the loading direction (H). Tan et al found that similar to observations in this paper, the horizontally printed maraging steel exhibited higher tensile strength then vertically printed specimens [21]. within the cells and through the cell boundaries in accordance with prior studies [17,19].…”
Section: Shown Insupporting
confidence: 91%
“…In printed samples where layering is perpendicular to the direction of the applied load, failure occurs before samples printed such that layers are parallel to the loading direction (H). Tan et al found that similar to observations in this paper, the horizontally printed maraging steel exhibited higher tensile strength then vertically printed specimens [21]. within the cells and through the cell boundaries in accordance with prior studies [17,19].…”
Section: Shown Insupporting
confidence: 91%
“…The morphology of the sample produced using 44 J/mm 3 showed irregular pores with unconsolidated particles, which is characteristic of lack of fusion defects caused by insufficient heat input [14]. At E v of 267 J/mm 3 , the sample exhibited a significant number of spherical pores, which is characteristic of keyhole defects [32,33]. In contrast, the sample produced at 67 J/mm 3 showed few fine pores, which resulted in a higher relative density.…”
Section: Defects and Densificationmentioning
confidence: 98%
“…Selective laser melting (SLM) is a kind of state‐of‐the‐art processing technology that manufactures components in an incremental layer‐by‐layer means using the laser to melt, bond, and solidify powder particles on powder bed . It has been widely used in the production of a variety of alloys including titanium alloys, aluminum alloys, and stainless steel, providing the possibility for its application in producing tungsten. Tan et al .…”
Section: Introductionmentioning
confidence: 99%